Designer seed treatment techniques on enhancement of yield in paddy - Sujatha, K; Ambika, S (ORYZA-An International Journal of Rice, 2018)
Field experiments were carried out at Agricultural Research Station, Vaigai Dam to identify the performance of designer seed on yield of paddy. Seeds fortified with KCl 1% for 6 h followed by polymer coating @ 3ml/ kg + Carbendazim @ 2 g/kg + Imidachloprid @ 2 ml/kg + Trichoderma viride @ 4 g/kg + Azospirillum @ 40 g /kg.The effect was more beneficial through increased plant height, no. of productive tillers/plant, no. of. seeds/panicle, seed yield/plant (g) and seed yield/ ha (kg) compared to untreated control. Days to 50% flowering and pest and disease incidence (%) were higher in untreated control.